Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How can I evaluate the following series: $$1+\frac{3}{4}+\frac{3\cdot 5}{4\cdot 8}+\frac{3\cdot 5\cdot 7}{4\cdot 8\cdot 12}+\frac{3\cdot 5\cdot 7\cdot 9}{4\cdot 8\cdot 12\cdot 16}+\cdots$$ In one book I saw this sum is equal to $\sqrt{8}$, but I don't know how to evaluate it.

share|improve this question
    
Since you indicate this is homework it would assist in giving you a good answer if you give some more context. Homework in which course? Which theorems were taught in relation to this exercise? –  Ittay Weiss Dec 28 '12 at 9:02
1  
possible duplicate math.stackexchange.com/questions/207062/sum-of-the-series/… –  clark Dec 28 '12 at 9:30
    
This is a binomial series. –  Lucian May 10 at 15:18

2 Answers 2

up vote 25 down vote accepted

$$a_n = \dfrac{1 \cdot 3 \cdot 5 \cdot 7 \cdots (2n+1)}{4 \cdot 8 \cdot 12 \cdots (4n)} = \dfrac{1 \cdot 3 \cdot 5 \cdot 7 \cdots (2n+1)}{4^n \cdot n!} = \dfrac{(2n+1)!}{2^n \cdot 4^n \cdot n! \cdot n!} = \dfrac1{8^n} \dfrac{(2n+1)!}{n! \cdot n!}$$ Now consider $f(x) = \dfrac1{(1-4x)^{3/2}}$. The Taylor series of $f(x)$ is $$f(x) = \sum_{n=0}^{\infty} \dfrac{(2n+1)!}{n! \cdot n!} x^n$$ and is valid for $\vert x \vert < \dfrac14$. Hence, we get that $$\sum_{n=0}^{\infty}\dfrac1{8^n} \dfrac{(2n+1)!}{n! \cdot n!} = f(1/8) = \dfrac1{(1-4\cdot 1/8)^{3/2}} = 2^{3/2} = \sqrt{8} = 2\sqrt{2}$$

EDIT

Below is a way on how to pick the appropriate function. First note that $$\dfrac{1 \cdot 3 \cdot 5 \cdot 7 \cdots (2n+1)}{2^n} = (-1)^n \times \left(-\dfrac32\right) \times \left(-\dfrac32-1\right) \times \left(-\dfrac32-2\right) \times \cdots \times \left(-\dfrac32-n+1\right)$$ $$a_n = \dfrac1{2^n}\dfrac{(-1)^n \times \left(-\dfrac32\right) \times \left(-\dfrac32-1\right) \times \left(-\dfrac32-2\right) \times \cdots \times \left(-\dfrac32-n+1\right)}{n!}$$ Hence, $a_n = \left(\dfrac{-1}{2}\right)^n \dbinom{-3/2}{n}$. Hence, the idea is to consider $$g(x) = \sum_{n=0}^{\infty} \dbinom{-3/2}{n} x^n = (1+x)^{-3/2}$$ The motivation to choose such a $g(x)$ comes from the fact that $$(1+x)^{\alpha} = \sum_{n=0}^{\infty} \dbinom{\alpha}{n} x^n$$ where $\dbinom{\alpha}{n}$ is to be interpreted as $\dfrac{\alpha(\alpha-1)(\alpha-2)\cdots(\alpha-n+1)}{n!}$ forall real $\alpha$.

Now set $x=-1/2$ to get that $$g(-1/2) = (1/2)^{-3/2} = 2^{3/2} = \sqrt{8} = 2\sqrt{2}$$

Once we have $g(x)$, we could either have it as such or we can play around with some nice scaling factor, to choose the function $f(x) = (1-4x)^{-3/2}$ to get the Taylor series $$\sum_{n=0}^{\infty} \dfrac{(2n+1)!}{n! \cdot n!}x^n$$

share|improve this answer
4  
It might help to have a comment on how you came to pick the particular function $f(x)$ ... since that would help to give insight into other similar problems –  Mark Bennet Dec 28 '12 at 8:47
1  
@MarkBennet Thanks. Have added it now. –  user17762 Dec 28 '12 at 9:17
    
Very helpful - thanks. –  Mark Bennet Dec 28 '12 at 9:19

The series can be written as $$1+\left(-\frac{3}{2}\right)\left(-\frac{1}{2}\right)+\frac{1}{2!}\left(-\frac{3}{2}\right)\left(-\frac{3}{2}-1\right)\left(-\frac{1}{2}\right)^2+\frac{1}{3!}\left(-\frac{3}{2}\right)\left(-\frac{3}{2}-1\right)\left(-\frac{3}{2}-2\right)\left(-\frac{1}{2}\right)^3+\cdots$$ which by binomial theorem is nothing but $(1-1/2)^{-3/2}=2^{3/2}=\sqrt{8}$

share|improve this answer
    
really smart solution! –  007resu Dec 28 '12 at 9:38
    
Brilliant solution. Concise and uses just binomial theorem –  Aditya Sriram Dec 28 '12 at 13:31

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.